Influence of extended pi-conjugation units on carrier mobilities in conducting polymers - Harima, Yutaka; Kim, D. H.; Tsutitori, Y.; Jiang, Xiaoqing; Patil, R.; Ooyama, Y.; Ohshita, J.; Kunai, A. (Chemical Physics Letters, 2006)
Carrier mobilities in thin films of copolymers with repeat units consisting of oligothiophenes bridged by Si atoms are measured over a range of doping levels, where the numbers of thienylenes in the repeat unit are 7, 8, 10, 12, and 14. The mobilities for these polymer films increased with the increase in doping level and the mobility enhancement followed an increasing order of the pi-conjugation length. The magnitude of the mobility increase for the Si polymer comprising 14 thiophene units reached ca. 10(4), implying that this pi-conjugation length is almost sufficient to reproduce transport properties of polythiophenes. (c) 2006 Elsevier B.V. All rights reserved.

Toluene alkylation with methanol to p-xylene over heteropoly acids supported by clay - Bokade, Vijay V.; Deshpande, Suvarna S.; Patil, R.; Jain, S.; Yadav, G. D. (Journal of Natural Gas Chemistry, 2007)
{The alkylation of toluene with methanol for the selective formation of p-xylene was systematically studied. Very few studies have been reported on the use of superacids such as heteropolyacids on cheap supports, such as clay. This article deals with the use of different heteropoly acids (HPAs), viz, Dodeca-Tungstophosphoric acid [
Keywords: co-crystalline; p-xylene; toluene alkylation; ZSM-12; ZSM-5

Synthesis of Ag-Pt alloy nanoparticles in aqueous bovine serum albumin foam and their cytocompatibility against human gingival fibroblasts - Singh, A. V.; Patil, R.; Kasture, M. B.; Gade, Wasudeo N.; Bhagavatula L. V. Prasad (Colloids and Surfaces B-Biointerfaces, 2009)
Foams of bovine serum albumin (BSA) have been utilized for synthesizing in situ protein capped Ag-Pt alloy nanoparticles. The in vitro cytotoxicity and the rate of proliferation of human gingival fibroblasts (HGFs) in presence of the above synthesized alloy nanoparticles is investigated. Expression profile of protein involved in detoxification, i.e. metallotheonein (MT) were assayed by ELISA and expression of mRNA transcripts by reverse transcription polymerase chain reaction (RT-PCR). Cytotoxicity results suggested that protein capped nano-alloys might be promising candidates for implants and prosthetic material. RT-PCR and ELISA confirmed the expression of MT. in cells treated with the alloy nanoparticles. Morphology variation studied by SEM also confirms that cells treated with alloy nanoparticles present an intact morphology. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Alloy nanoparticles; Biocompatibility; ELISA; Human gingival fibroblasts; mRNA; Protein foams